Spreminjanje rabe tal v Sloveniji v obdobju 2000-2012 in prehranska varnost - Žiberna, Igor (Revija za geografijo, 2013)
Paper analyzes the processes of change in land use in Slovenia in the period 2000 - 2012 in the context of food security. Primarily processes of change in arable land in the national and municipal levels are presented. Changes in land use in Slovenia according to the selected physical geographical indicators that affect the production potential (altitude, slope, aspect, global solar radiation, floor number) are also analyzed.
Keywords: agriculture; Filozofska fakulteta; food; kmetijstvo; Maribor; Oddelek za geografijo; poljedelstvo; prehrana; raba tal; Slovenia; Slovenija; varna hrana